Spatial Dynamics of Land Cover Change in the Ngata Toro Customary Forest, Toro Village, Kulawi District, Sigi Regency, from 2021 to 2025 - Cesar A. Mappatoba; Imran Rachman; Adam Malik; Golar; Sudirman Dg. Massiri; Andi Sahri Alam (Postgraduate, University of Mataram, 2025)
Customary forests play a crucial role in maintaining ecosystem balance, biodiversity, and the sociocultural sustainability of local communities. However, pressure on forest cover continues to increase due to land clearing and conversion. This study was conducted from February to July 2025 in the Ngata Toro Customary Forest, Toro Village, Kulawi District, Sigi Regency, to analyze land cover changes from 2021 to 2025 using satellite imagery and the Object-Based Image Analysis (OBIA) segmentation method. The results show a decrease in forest area from 1,604.16 ha (2021) to 1,475.98 ha (2025), or a decrease of approximately 128.18 ha (7.99%), accompanied by an increase in non-forest area from 140.99 ha to 268.88 ha. Initial changes occurred in high-access areas near settlements and roads, then spread inland, leading to forest fragmentation. Peak deforestation occurred in 2024, with a decrease of 57.49 ha in one year. Spatial patterns show a close relationship between deforestation and accessibility, topography, and agricultural intensification. Classification accuracy tests yielded an overall accuracy of 80–85%, with the highest in 2021 and the lowest in 2023. Fragmentation reduces habitat connectivity, threatens wide-ranging species, and degrades ecosystem functions such as carbon storage and hydrological regulation. These results underscore the importance of ecosystem-based management strategies and controlled land clearing to maintain the ecological integrity of customary forests.